2022
DOI: 10.3390/cells12010052
|View full text |Cite
|
Sign up to set email alerts
|

CLPP Depletion Causes Diplotene Arrest; Underlying Testis Mitochondrial Dysfunction Occurs with Accumulation of Perrault Proteins ERAL1, PEO1, and HARS2

Abstract: Human Perrault syndrome (PRLTS) is autosomal, recessively inherited, and characterized by ovarian insufficiency with hearing loss. Among the genetic causes are mutations of matrix peptidase CLPP, which trigger additional azoospermia. Here, we analyzed the impact of CLPP deficiency on male mouse meiosis stages. Histology, immunocytology, different OMICS and biochemical approaches, and RT-qPCR were employed in CLPP-null mouse testis. Meiotic chromosome pairing and synapsis proceeded normally. However, the foci n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 149 publications
3
9
0
Order By: Relevance
“…All other ribonucleoproteins were assessed, and 16 candidates were conspicuous in all three tissues (Figure S2), with translation factors occupying a prominent place. Among the disease proteins responsible for Perrault syndrome, HARS2 was prominent because of its strong accumulation in CLPP-null tissue, as previously reported upon quantitative immunoblots [17], and here, the complexomics profile revealed a parallel distribution of CLPX and HARS2 from their monomeric sizes (precursors of 69 and 23 kDa, respectively) up to molecular sizes around 250 kDa. Similarly, a close co-migration with CLPX was documented for GFM1 from its monomeric size (84 kDa) to positions around 250 kDa, in addition to very strong accumulation (average 10-fold).…”
Section: Co-migration Of Mtssu Monomeric Factors With Eral1 As Expect...supporting
confidence: 88%
See 1 more Smart Citation
“…All other ribonucleoproteins were assessed, and 16 candidates were conspicuous in all three tissues (Figure S2), with translation factors occupying a prominent place. Among the disease proteins responsible for Perrault syndrome, HARS2 was prominent because of its strong accumulation in CLPP-null tissue, as previously reported upon quantitative immunoblots [17], and here, the complexomics profile revealed a parallel distribution of CLPX and HARS2 from their monomeric sizes (precursors of 69 and 23 kDa, respectively) up to molecular sizes around 250 kDa. Similarly, a close co-migration with CLPX was documented for GFM1 from its monomeric size (84 kDa) to positions around 250 kDa, in addition to very strong accumulation (average 10-fold).…”
Section: Co-migration Of Mtssu Monomeric Factors With Eral1 As Expect...supporting
confidence: 88%
“…Mutations in human CLPP cause Perrault syndrome type 3 (PRLTS3), an autosomal recessive disorder characterized by complete infertility due to female primary ovarian insufficiency and male azoospermia after meiotic arrest at diplotene, with subsequent sensorineural deafness, followed by insidious neurodegeneration manifesting as ataxia, leukodystrophy, and neuropathy [16,17]. Most variants of Perrault syndrome are triggered by the failure of mitochondrial RNA processing and translation, as exemplified by other causal mutations in the tRNA-amino acid synthases HARS2 and LARS2, in the mitoribosomal factor RMND1, in the RNA degradation factor PRORP, in the nucleoid replication/repair factor TWNK, or in CLPP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with controls, the ClpP cKO spermatocytes expressed more ClpX protein, and vice versa for the ClpX cKO spermatocytes. The observation is in line with a previous study showing remarkable ClpX accumulation in many organs, including testis and ovary of ClpP deleted mice 26 , 37 . The ClpP/ClpX cKO testes were smaller than the controls.…”
Section: Discussionsupporting
confidence: 93%
“…CLPP is the key regulator of the mtUPR pathway. Mutations in the mitochondrial protease CLPP result in Perrault syndrome type 3 (PRLTS3), an autosomal recessive disorder characterized by complete infertility due to female primary ovarian insufficiency and male azoospermia after meiotic arrest at diplotene, with sensorineural deafness, ataxia, leukodystrophy, and neuropathy [11][12][13]. Previous studies have shown that global germline Clpp deficiency in female mice results in impaired oocyte maturation, abnormal formation of twocell embryos, and blastocyst development failure, ultimately leading to infertility [14,15].…”
Section: Introductionmentioning
confidence: 99%